Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1089/neu.2017.5191
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Dual-Task Gait after Concussion and Prolonged Symptom Duration

Abstract: Quantitative gait measurements can identify persistent postconcussion impairments. However, their prognostic utility after injury to identify the likelihood of prolonged concussion symptoms remains unknown. Our objective was to examine if dual-task gait performance measures are independently associated with persistent (> 28 days) concussion symptoms among a sample of athletes. Sixty individuals diagnosed with a sport-related concussion were assessed within 10 days of their injury. Each participant completed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 48 publications
0
21
1
Order By: Relevance
“…[32][33][34] Others have reported that VR may speed up recovery after concussion. 34 Factors that may affect outcome negatively for patients postconcussion include immediate dizziness, 35 larger changes in gait speed and cadence with dual tasks while walking, 36 anxiety or depression, 37 greater number of symptoms and symptom severity, 38 and the complaint of fogginess. 25…”
Section: Central Vestibular Disordersmentioning
confidence: 99%
“…[32][33][34] Others have reported that VR may speed up recovery after concussion. 34 Factors that may affect outcome negatively for patients postconcussion include immediate dizziness, 35 larger changes in gait speed and cadence with dual tasks while walking, 36 anxiety or depression, 37 greater number of symptoms and symptom severity, 38 and the complaint of fogginess. 25…”
Section: Central Vestibular Disordersmentioning
confidence: 99%
“…Having a greater number and more severe symptoms after a concussion, acute headaches, poor acute balance deficits, poor dual-task gait function, and acute neuropsychological deficits have each been identified as potential predictors of slower recovery. 12,17,18,24,31,32 Recently, researchers have established a clinical paradigm to determine the PPCS risk among pediatric patients presenting to the ED. 31 The ED-validated Predicting Persistent Post-concussive Problems in Pediatrics (5P) clinical risk score incorporates several clinical domains to predict the future PPCS risk, including demographics, medical history, initial symptoms, cognitive symptoms, and physical abilities.…”
mentioning
confidence: 99%
“…Participants wore 3 inertial measurement sensors (Opal sensor; APDM, Inc, Portland, OR) attached to the lumbar spine at the lumbosacral junction and to the dorsum of each foot with an elastic belt. 13,21 Data were obtained at the sampling frequency of 128 Hz. For these devices, the industrial, scientific, and medical (ISM) radio frequency was 2.40 to 2.48 GHz, the calibrated frequency ranged from 150 kHz to 80 MHz, and the synchronization between devices was 1 millisecond or less.…”
Section: Data Processing and Analysismentioning
confidence: 99%
“…We calculated average walking speed, an established linear measure, using Mobility Lab 2.0 (APDM, Inc). 13,21 We included average walking speed as an independent outcome because CRQA quantifies the underlying organization of gait variability, regardless of average walking speed, and provides an index of gait-speed pattern around the mean, whereas the average gait speed gives a global walking behavior description. We did not use gait speed or trial length as covariates in our analysis, as our radius parameter value ensured that each cross-recurrence plot maintained a fixed recurrence value (ie, 5%), thus controlling for trial length by forcing each plot to contain a fixed number of recurrent points.…”
Section: Gait Speedmentioning
confidence: 99%